Social Competence: Essence and Mechanisms of Formation in a Preschooler with Speech Impairment (Texas Journal of Engineering and Technology, 2023)
The article discusses the issue of social competence, the essence and mechanisms of formation in a preschooler with speech impairment. The main attention is paid to identifying key competencies and areas of the competency-based approach in modern education